The Online Visibility of the Romanian Hotels. Emphasis on the Hotels from the North-East Region of Romania - Andreea Maha (CES Working Papers, 2015)
The purpose of the present research is to analyze the online visibility of Romanian hotel websites and what mistakes are identified once we analyze the hotel content. At the same time we want to provide a complex overview of how Romanian hotels use the Internet for their business. The research method used for creating this article is documentary study and content analysis. We have carried out the content analysis of all hotel websites categorized between 3 to 5 stars in the North-East region of Romania. The main mistakes identified consist in the use of websites just for information purposes, the information are often not up to date which promote hotels that no longer exist, and not allow reservations/payments in real time. Many links and services that apparently exist on the website are inactive.
Keywords: L83; 330; hotel; North-East region of Romania; content analyze; website; online visibility